Performance Analysis and Ranking of Corporate Medical Institutions in India - Nanda, Susama; Mishra, Manoj; Ramesh, Dola Babu (DESIDOC Journal of Library & Information Technology, 2018)
Health science research focuses to generate new knowledge through new technique, research design and organisational interventions to serve the whole community. The corporate Medical colleges are determined to establish themselves in both academic and research purpose. The performance index (P-index) is an interesting parameter to calculate the ranking performance of any institution. This study presents an analysis of the research growth, collaboration of researchers with ranking of the corporate medical institutes in India according to p-index.